THE FUTURE OF JOBS IN THE AGE OF ARTIFICIAL INTELLIGENCE - Davronov Murodjon Abrorovich; Ma’ripov Jalolkhan Kamoliddin ugli (Economics, management, and digital innovation in education: contemporary trends and approaches, 2025)
Artificial Intelligence (AI) is revolutionizing industries and redefining the global workforce. This paper examines the influence of AI on future employment, highlighting both the potential threats and opportunities. While automation may replace certain jobs, AI also creates new career paths and enhances human productivity. By understanding these trends, societies can prepare for a balanced integration of AI into the labor market.